2022
DOI: 10.1029/2021jb022663
|View full text |Cite
|
Sign up to set email alerts
|

Rupture Heterogeneity and Directivity Effects in Back‐Projection Analysis

Abstract: The back projection method is a tremendously powerful technique for investigating the time dependent earthquake source, but its physical interpretation is elusive. We investigate how earthquake rupture heterogeneity and directivity can affect back‐projection results (imaged location and beam power) using synthetic earthquake models. Rather than attempting to model the dynamics of any specific real earthquake, we use idealized kinematic rupture models, with constant or varying rupture velocity, peak slip rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 83 publications
(148 reference statements)
1
13
0
Order By: Relevance
“…The near-perfect consistency of the polarities, and the good agreement of the P -to-S wave ratio between data and synthetics are governed by the source moment tensor properties that have been obtained from first motion polarity data (Hillers et al, 2020). The few visible inconsistencies between data and synthetics such as the S-wave properties at the N channel of the HEL1, PK01, KUN, and MKK stations suggest a small degree of structural heterogeneity, which is compatible with wave propagation phenomena inferred with array analysis techniques (Taylor et al, 2021;Li et al, 2022).…”
Section: Comparison Of Seismic and Acoustic Observations And Syntheticssupporting
confidence: 56%
“…The near-perfect consistency of the polarities, and the good agreement of the P -to-S wave ratio between data and synthetics are governed by the source moment tensor properties that have been obtained from first motion polarity data (Hillers et al, 2020). The few visible inconsistencies between data and synthetics such as the S-wave properties at the N channel of the HEL1, PK01, KUN, and MKK stations suggest a small degree of structural heterogeneity, which is compatible with wave propagation phenomena inferred with array analysis techniques (Taylor et al, 2021;Li et al, 2022).…”
Section: Comparison Of Seismic and Acoustic Observations And Syntheticssupporting
confidence: 56%
“…The basic principle of the back-projection method relies on the coherence of signals generated by the dense seismic arrays utilised to image the source characteristics [18,19,20]. A recent study working on the effects of rupture heterogeneity and directivity on back-projection imaging results has found that the image results are affected by the source frequency distribution and the array configuration [21]. This is complementary to previous studies (e.g.…”
Section: Introductionmentioning
confidence: 81%
“…It is not clear whether such rupture deceleration is controlled by a self‐evolving mechanism (featuring a dynamically self‐chosen rupture path) (Kame & Yamashita, 1999), or is caused by the encountering of a preexisting fault barrier (Xu & Ben‐Zion, 2013). In any case, the activated splay faults (Figure 12b), the pronounced aftershock activity (Figure 12a), and the complementary relation between local slip minimum and local off‐fault deformation maximum at ∼50 km (at W3 and E2 in Figure 12b) from the mainshock epicenter (He et al., 2022; Jin & Fialko, 2021; C. Li et al., 2023; Yuan et al., 2022) imply the involvement of some strengthening mechanism near the ends of the main fault, which can support the prediction of Xu and Ben‐Zion (2013) for sudden rupture deceleration.…”
Section: Discussionmentioning
confidence: 99%
“…The red stars, green squares, and cyan diamonds show the rupture speeds of the eastern fault and the western fault from the backprojection studies in this study, Q. Li et al (2022), and X. .…”
Section: The Relation Among Fault Structure Damage Pattern and Earthq...mentioning
confidence: 90%